Analisis Pengaruh Human Capital dan Structural Capital terhadap Kinerja Perusahaan - Kafidin Muzakki (2477 - 6165, 2020)
The research wants to test and analyse using a quantitative approach whether the existence of human capital and structural capital has an influence on company performance as measured by Economic Value Added (EVA). The population of this study is the financial statements of pharmaceutical manufacturing companies listed on the Indonesia Stock Exchange (BEI) from 2013 to 2018, with a sample size of 6 companies, the number of observations was 36 samples. The results of this study indicate that the management of human capital and structural capital has a positive but insignificant effect on company performance as measured by Economic Value Added (EVA) assessments, so that theoretically it does not support Barney and Clark's Resource Based Theory (RBT) theory, because there are still components of human capital and structural capital which quantitatively have a positive but insignificant effect. RBT theory states that companies have three types of resources, namely human resources (HR), organizational/structural resources, and physical resources that contribute to obtaining profitability. The three types of resources are an integral part that cannot be separated because they influence one another.